THE CORRELATION BETWEEN STUDENTS’ READING MOTIVATION AND THEIR READING COMPREHENSION AT TENTH GRADE STUDENTS OF SMAN 6 KOTA TANGERANG IN ACADEMIC YEAR 2018/2019 - Anis Nurul Hanifah; Agus Mulyana; Hery Nuraini (JIPIS, 2018)
AbstractThe purpose of the research was to find out and analyze the positive correlation between the students’ reading motivation and their reading comprehension at tenth grade students of SMAN 6 Kota Tangerang in academic years 2018/2019. The population of the research was the whole classes of tenth grade students of SMAN 6 Kota Tangerang which consist of 378 students. Then, there were 79 students was selected as the sample of the research by using Simple Random Sampling. The data were collected by using MRP-R Reading Survey to test students’ reading motivation (variable X) and Short Answer Task to test students’ reading comprehension (variable Y). The result of this research can prove the hypothesis that showed there is correlation between students’ reading motivation and their reading comprehension. In other hand, if students’ reading motivation is high then their reading comprehension will also high. So, it can be concluded that there is positive correlation between students’ reading motivation and their reading comprehension at tenth grade students of SMAN 6 Kota Tangerang in academic years 2018/2019.Keywords: correlation, reading comprehension, reading motivation AbstrakTujuan dari penelitian ini adalah untuk mencari tau dan menganalisa hubungan positif antara motivasi membaca siswa dan pemahaman membaca siswa kelas 10 di SMAN 6 Kota Tangerang tahun ajaran 2018/2019. Populasi dari penelitian ini adalah semua kelas 10 dari SMAN 6 Kota Tangerang yang terdiri dari 378 siswa. Kemudian, di ambil 79 siswa sebagai sampel penelitian menggunakan teknik Simple Random Sampling. Data yang di kumpulkan menggunakan MRP-R Reading Survey untuk menguji motivasi membaca siswa (variabel X) dan Short Answer Task untuk menguji pemahaman membaca siswa (variabel Y). Hasil dari penelitian ini dapat membuktikan hipotesis yang menyatakan bahwa terdapat korelasi antara motivasi membaca siswa dan pemahaman membaca siswa. Dengan kata lain, semakin tinggin motivasi membaca siswa maka pemahaman membaca siswa akan tinggi juga. Jadi, dapat disimpulkan ada hubungan yang positif antara motivasi membaca siswa dan pemahaman membaca siswa kelas 10 di SMAN 6 Kota Tangerang tahun ajaran 2018/2019.Kata Kunci: korelasi, motivasi membaca, pemahaman membaca